Measurement of the three-axis vibration, temperature, and relative humidity profiles of commercial transport trailers for pigs. (28th January 2021) - Morris, Benjamin K; Davis, R Benjamin; Brokesh, Edwin; Flippo, Daniel K; Houser, Terry A; Najar-Villarreal, Francisco; Turner, Kari K; Williams, Jamison G; Stelzleni, Alexander M; Gonzalez, John M
Abstract: The objective of this study was to collect and interpret three-axis acceleration, temperature, and relative humidity data from six locations within commercial transport trailers shipping market-weight pigs. Transport was observed in Kansas ( n = 15) and North Carolina ( n = 20). Prior to loading, three-axis accelerometers were affixed to six locations on the trailers: top fore (TF), top center (TC), top aft (TA), bottom fore (BF), bottom center (BC), and bottom aft (BA) compartments. Data were post-processed to calculate root-mean-square (RMS) accelerations and vibration dose values (VDV) in the vertical direction and the horizontal plane. These values were compared with exposure action values (EAV) and exposure limit values (ELV), vibration levels deemed uncomfortable and potentially dangerous to humans. Additionally, RMS and VDV were compared among the trailer compartments. The vertical RMS accelerations for all compartments exceeded the EAV for loads measured in Kansas, and for the majority of the compartments measured in North Carolina. Many compartments, specifically the BA compartment from all trips, exceeded the vertical ELV. Regardless of where the data were collected, fewer compartments exceeded the EAV in the horizontal orientation. Only BA compartments exceeded the ELV in the horizontal orientation. There were Area × Level interactions for vertical and horizontal RMS and VDV ( P < 0.01). The BF compartment had a greater vertical RMS value than the TF, TC, and BC ( P < 0.02) compartments, but did not differ ( P = 0.06) from the TA compartment. The vertical RMS of the TA compartment did not differ from the TF, TC, and BC compartments ( P > 0.13). The BF compartment had a greater ( P = 0.02) vertical VDV value than the TC location, but did not differ from the other locations ( P > 0.16). All other locations did not differ in vertical VDV ( P > 0.12). The BF compartment had greater horizontal RMS than the TC and TA compartments ( P < 0.01), but did not differ from TF and BC compartments ( P > 0.12). All other compartments did not differ in horizontal RMS ( P > 0.34). All compartments, aside from the BA compartment, did not differ in horizontal VDV ( P > 0.19). Vibration analyses indicated the BA compartment had the greatest vertical and horizontal vibrations and a large percentage of the compartments exceed the EAV and ELV, which indicated pigs may have experienced uncomfortable trips that could cause discomfort or fatigue.